Unusual clinical presentation of anaplastic large cell lymphoma - Fernando Peixoto Ferraz de Campos; Maria Claudia Nogueira Zerbini; Aloisio Felipe-Silva; Angélica Braz Simões; Silvana Maria Lovisolo; Leonardo Gomes da Fonseca; Lorena Laborda (Autopsy and Case Reports, 2014)
Anaplastic large cell lymphoma (ALCL), a well-recognized entity, presents a varied clinical picture and epidemiological characteristics associated with the expression of the anaplastic lymphoma kinase (ALK) protein. When classic symptoms are present (weight loss, fever, and night sweats) and combine with enlarged and easily accessible peripheral lymph nodes, diagnosis is not that difficult. But when the clinical presentation is nonspecific, a tough diagnostic task is required. HIV infection is highly associated with neoplastic disorders—mainly with those of hematological origin. However, ALCL is exceptionally associated with HIV infection, and the few reported cases are ALK– ALCL. The authors report two cases of ALK+ ALCL with the unusual clinical presentation: one is associated with the HIV infection and the other presents as a fever of unknown origin (FUO) without peripheral lymphadenopathy. The latter was autopsied and was characterized by nodal and extra nodal involvement. The authors call attention to the plurality of clinical presentation of this group of lymphomas, and the early indication of bone marrow examination in cases of an FUO with elevated hepatic enzymes and lactic dehydrogenase.